2022
DOI: 10.1155/2022/7942845
|View full text |Cite
|
Sign up to set email alerts
|

Scientific Evidence of Chinese Herbal Medicine (Gegen Qinlian Decoction) in the Treatment of Ulcerative Colitis

Abstract: Objectives. Gegen Qinlian decoction (GQD), a Chinese herbal compound, has been widely used in the treatment of ulcerative colitis (UC) in China. However, evidence from systematic reviews (SRs)/meta-analyses (MAs) of GQD in UC remains highly controversial. To collate, evaluate, and synthesize the current evidence, we carried out this study. Methods. SRs/MAs of GQD for UC were obtained from eight databases. Methodological Quality of Systematic Reviews 2 (AMSTAR-2) was utilized to appraise the methodological qual… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
19
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 17 publications
(20 citation statements)
references
References 21 publications
0
19
0
Order By: Relevance
“…23 -36 However, not all SR/MAs were reported according to PRISMA standards or had the assessment of evidence quality by GRADE. 37,38 In such cases, an overview of SRs/MAs is preferable to the large number of SRs/MAs of lower quality and with less convincing conclusions. 39,40 In addition, an overview can provide limitations that are worth noting and need improvement to drive future high-quality SRs/MAs.…”
Section: Discussionmentioning
confidence: 99%
“…23 -36 However, not all SR/MAs were reported according to PRISMA standards or had the assessment of evidence quality by GRADE. 37,38 In such cases, an overview of SRs/MAs is preferable to the large number of SRs/MAs of lower quality and with less convincing conclusions. 39,40 In addition, an overview can provide limitations that are worth noting and need improvement to drive future high-quality SRs/MAs.…”
Section: Discussionmentioning
confidence: 99%
“…Finally, we discussed the evidence of TCM alleviates UC by regulating macrophage polarization and the potential mechanism of TCM regulating macrophage polarization in the treatment of UC. patterns of UC patients were large intestine dampness-heat, followed by spleen-kidney yang deficiency, liver depression and spleen deficiency, spleen-stomach weakness, and spleen deficiency with dampness accumulation, which reflected the progress of UC with different phases (Zhang X. et al, 2022). For UC patients with CM pattern of Large intestine dampnessheat, which clear heat and dampness, harmony qi and blood are needed; For UC patients with CM pattern of Spleen-kidney yang deficiency, which warm and tonify spleen and kidney are needed; For UC patients with CM pattern of liver depression and spleen deficiency, which sooth liver and strengthen spleen are needed; For UC patients with CM pattern of spleenstomach weakness, which tonify the spleen and stomach are needed; For UC patients with CM pattern of Spleen deficiency with dampness accumulation, which tonify spleen and resolve dampness are needed (Zhang X. et al, 2022).…”
Section: Introductionmentioning
confidence: 94%
“…Gegen Qinlian decoction, a classic TCM compound, encompasses Radix Puerariae , Scutellariae , Coptidis Rhizom a, and Licorice . Recent research showed that Gegen Qinlian decoction combined with CWM seemed to be more effective in UC than CWM treatment alone ( Huang et al, 2022 ). A systematic review of randomized controlled trials including 2028 UC patients showed consistent results that Gegen Qinlian decoction treatment alone or Gegen Qinlian decoction combined with CWM treatment had potential benefits in curing UC ( Fan Y. et al, 2019 ).…”
Section: Tcm Alleviates Uc By Regulating Macrophage Polarizationmentioning
confidence: 99%
See 1 more Smart Citation
“…Systematic reviews (SRs)/meta-analyses (MAs) are considered the highest level of evidence in evidence-based medicine, yet inconsistent results may interfere with evidence-based decision-making [ 11 , 12 ]. BXD has been widely used in the treatment of GERD in China and is highly effective due to its multicomponent and multitarget characteristics [ 13 ].…”
Section: Introductionmentioning
confidence: 99%